PEMBERDAYAAN LINGKUNGAN STUDI PERANAN SRIATUN DALAM PEMBERDAYAAN LINGKUNGAN MELALUI PENDIDIKAN DAUR ULANG DI DESA PEKULO KECAMATAN GENTENG KABUPATEN BANYUWANGI - Muhammad Iqbal (AT TAMKIN : Jurnal Pengembangan Masyarakat Islam dan Perubahan Sosial, 2021)
This study aims to know what part Sriatun in the empowerment of the environment in Pekulo village, subdistrict Genteng, district Banyuwangi. In addition this research also Aims to know empowerment forms what happened in village Pekulo environment, subdistrict Genteng, district Banyuwangi. Qualitative descriptive approach was used in the study . Data collection techniques used in this research was observation , interviews and documentation .The results of this study is the role of research in the empowerment Sriatun environment there are several the role of which are (1) as enabler, (2) as a broker, (3) as the cadres. While empowerment forms that happens through environment (1) conservation environmental, (2) through recycling garbage.